The Influence of Silane Gas Flow Rate on Optoelectronic Properties of µc-Si:H Prepared by HWC-VHF-PECVD Technique - T. Winata; I. Usman (Institute for Research and Community Services (LPPM) ITB, 2008)
Hydrogenated microcrystalline silicon (µc-Si:H) thin films have been deposited using 10% silane (SiH4) in H2 dilution by Hot Wire Cell Very High Frequency Plasma Enhanced Chemical Vapor Deposition (HWC-VHF-PECVD) technique. The resulted thin film characteristics were systematically studied as a function of the deposition parameter. The previous structural studies showed that the structural phase transition from amorphous to microcrystalline thin film was obtained using the filament temperature of 800 °C. In this study, the optoelectronic properties of µc-Si:H thin films were investigated as a function of the silane gas flow rate from 40 sccm to 80 sccm. The highest deposition rate of 3.6 A/sec and the lower optical bandgap of 1.4 eV were obtained using 80 sccm and 60 sccm of the silane gas flow rate, respectively. The film showed the photosensitivity of 3 x 107, which is quite high above the minimal value of 103 for solar cell application.